THE MODERATING EFFECT OF INDEPENDENT COMMISIONERS ON FINANCIAL POLICY AND PUBLIC OWNERSHIP TOWARD CORPORATE FINANCIAL PERFORMANCE - Niko Silitonga (International Journal of Contemporary Accounting, 2020)
AbstractThe corporate financial performance is one of the measurement instrument whether the company is sustainable. This study aims to determine the effect of financial policy and public ownership on corporate financial performance with Independence of commissioners as a moderating variable in mining companies listed on Indonesia Stock Exchanges. This research uses a quantitative research model using secondary data. The data in this study were processed by the Moderating Regression Analysis (MRA) method supported by the IBM SPSS and Microsoft Excel programs as support software with data analysis techniques in the form of a classic assumption test and R2 test, F test, and t test. The population in this study are companies that have reported annual reports consistently during the 2014-2017 period. This study used a purposive sampling technique and obtained as many as 19 companies in accordance with predetermined criteria. The results of this study indicate that financial policy proxied by debt policy (DER) has a significant and positive effect on corporate financial performance, public ownership has no significant effect on corporate financial performance, independence commissioners strengthen the relationship between financial policy on corporate financial performance and independence commissioners do not has a moderating role between the relationship between Public Ownership and corporate financial performance. This study uses data from mining sector companies, it is recommended for further research to use other sectors such as: Property & Real Estate Sector, Manufacturing Sector, and others listed on the Indonesia Stock Exchange. The implications of this study for the company management, this research can provide input to the company to be able to choose and use an independent commissioner who fulfills expertise in the financial and business fields of his company in order to make a decision on his company's financial policy.Keywords: Independence of Commissioners, Financial Policy, Public Ownership, Corporate Financial Performance.